PENGARUH TEKNIK RELAKSASI AUTOGENIK TERHADAP SKALA NYERI PADA PASIEN POST SPINAL ANESTESI DI RUMAH SAKIT PKU MUHAMMADIYAH GAMPING - Azizah, Aisyah Nur; Setyaki, Nanda Arya (Coping: Community of Publishing in Nursing; Vol 11 No 5 (2023): Oktober 2023DO - 10.24843/coping.2023.v11.i05.p10, 2023)
If pain management is not optimal, it has detrimental consequences, which can cause disorders in the endocrine, metabolic, immune, and other body systems with clinical manifestations in the form of fever, hypertension, etc. Post spinal anesthesia pain is defined as pain experienced after post anesthesia anesthesia. Pain conditions often occur in post-cesarean section patients. One therapy that can reduce pain in post-spinal anesthesia patients is the autogenic relaxation technique. Autogenic relaxation is relaxation that comes from oneself which can calm the mind. The aim of this study was to determine the effect of autogenic relaxation therapy on the pain scale in post spinal anesthesia patients at PKU Muhammadiyah Gamping Hospital. This research design uses a pre-experimental design with one group pretest-post test design with the Wilcoxon test. The sample in this study was post spinal anesthesia patients aged 20-60 years, a total of 51 respondents using purposive sampling. Data were collected using the Numeric Rating Scale pain assessment sheet. The results obtained were the highest number of respondents based on the post spinal anesthesia pain scale before therapy, namely moderate pain of 47 respondents (92,2%) and severe pain of 4 respondents (7,8%), based on the post spinal anesthesia pain scale after therapy, namely mild pain of 12 respondents (23,5%), moderate pain was 35 respondents (68,6%), and severe pain was 4 respondents (7,8%). The results of the Wilcoxon sign rank test showed a p value of 0,001<0,05. The conclusion of this study is that there is significant influence between autogenic relaxation techniques on the pain levels of post-spinal anesthesia patients at PKU Muhammadiyah Gamping.